A Shot at Visual Vulnerability Analysis. (June 2015) - Kerzner, Ethan; Butler, Lee A.; Hansen, Charles; Meyer, Miriah
Abstract Increasing the safety of vehicles is an important goal for vehicle manufacturers. These manufacturers often turn to simulations to understand how to improve a vehicle's design as real‐world safety tests are expensive and time consuming. Understanding the results of these simulations, however, is challenging due to the complexity of the data, which often includes both spatial and nonspatial data types. In this design study we collaborated with analysts who are trying to understand the vulnerability of military vehicles. From this design study we contribute a problem characterization, data abstraction, and task analysis for vehicle vulnerability analysis, as well as a validated and deployed tool called Shotviewer. Shotviewer links 3D spatial views with abstract 2D views to support a broad range of analysis needs. Furthermore, reflection on our design study process elucidates a strategy of view‐design parallelism for creating multiview visualizations, as well as four recommendations for conducting design studies in large organizations with sensitive data.